Pengembangan Media Pembelajaran Aplligung (Alat Peraga Lambung Dari Limbah Kulit Jagung) Terhadap Hasil Belajar Biologi Siswa Ma. Darussalam Al-Faisholiyah Sampang - Nur Hasanah; Wiwi Wikanta (Universitas Muhammadiyah Surabaya, 2018)
ABSTRACT:The research objectives are: 1). Understanding the physical feasibility of Aplligung as a learning media on the topic of the human digestive system specifically on stomach. 2). Understanding the feasibility of student learning outcomes by using Aplligung as a medium of learning on the topic of the human digestive system specifically on stomach. 3). Understanding the student's response toward the Aplligung as a learning media on gastric human digestion system topic, Research development of 4-D models (Four D Models). The phase of preparation procedure of Aplligung are (1) Needs analysis,(2) Initial product development and revision,(3) Material validation, media feasibility and revision,(4) Limited test, and(5) The final product. Questionnaire is used as the research instrument to know the feasibility of Aplligung. Validation of Aplligung was conducted by biology a teacher, two materials and media experts, and the observer consists of two Biology students and two teachers and responded by 27 students of science grade XI at MA Darussalam Al-Faisholiyah through a limited test. The data of quality valueare obtained in the form of qualitative processed into quantitative data and each aspect of the assessment is analyzed, the final score is converted into qualitative product feasibility level with guidelines by ideal category. The result of the development of learning media Aplligung shows that the validation of the material is very feasibleby 82.29%. Media feasibility assessment is very feasible by 81.25%. The assessment of student response is excellent by 94%. Exhaustiveness of learning results very well by 81.40%. The conclusion of the developed product is very feasible to use.Â